2012
DOI: 10.2460/javma.240.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-facilitated ankylosis of the distal intertarsal and tarsometatarsal joints in horses with osteoarthritis

Abstract: Intra-articular alcohol injection in horses with bone spavin resulted in a rapid (usually within 3 months) reduction in lameness and joint space collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
2
9
1
Order By: Relevance
“…The use of ethanol at 2 different concentrations was based on findings from Shoemaker et al [12] where a 95% concentration of ethanol appeared to produce a higher rate of joint fusion than 70%. This was in contrast to superior results obtained with 70% solutions in clinical cases as reported by Carmalt et al [13]. Our poor initial results obtained using 100% ethanol made us discontinue its use.…”
Section: Discussion Ethanolcontrasting
confidence: 64%
See 2 more Smart Citations
“…The use of ethanol at 2 different concentrations was based on findings from Shoemaker et al [12] where a 95% concentration of ethanol appeared to produce a higher rate of joint fusion than 70%. This was in contrast to superior results obtained with 70% solutions in clinical cases as reported by Carmalt et al [13]. Our poor initial results obtained using 100% ethanol made us discontinue its use.…”
Section: Discussion Ethanolcontrasting
confidence: 64%
“…Since the publication of Shoemaker's report [12], ethanol has been used to treat this condition, and the presentations by Bell et al [14] and Carmalt and Wilson [13] reported much better outcomes than those obtained in our study. We essentially followed the same treatment protocol, but a difference in population size, type, clinical history and the longer-term follow-up of our cases might account for this difference.…”
Section: Tarsal Diseasesupporting
confidence: 44%
See 1 more Smart Citation
“…Nevertheless, several medications are used intra-articularly, such as COs, hyaluronic acid (HA)/sodium hyaluronate (SH)/hyaluronate (HA), polysulfated glycosaminoglycans, sodium pentosan polysulfate, sodium chondroitin sulfate, somatostatin, N-acetyl- D-glucosamine, radiation synovectomy, dextrose prolotherapy, keratan sulfate orgotein, saline for washout, silicone, mucopolysaccharide polysulfuric acid ester, chloroquine, lactic acid solution, amikacin, gentamicin morphine, autologous serum, platelet-rich plasma, mesenchymal stem cells derived from bone marrow or adipose stromal vascular fraction, gene therapy using IL-1 antagonists, and ethanol. In addition, studies have used a topical liposomal formulation that contains diclofenac, lyophilized products from green-lipped mussel, extracorporeal shockwave, acupuncture, magnetic field, transcutaneous electrical nerve stimulation, therapeutic ultrasound, laser therapy, manual therapy, aquatic physical therapy and nutraceuticals food suplement (Uthman et al 2003;Caron 2005;Revenaugh 2005;Carmona et al 2007;Frisbie et al 2009;Goodrich and Nixon 2006;Santos et al 2009;Lindegaard et al 2010;Cayzer et al 2011;Kawcak et al 2011;Baccarin et al, 2012;McIIwraith et al 2011McIIwraith et al , 2012aCarmalt et al 2012;Lamas et al 2012;Vanderweerd et al 2012;Frisbie et al 2013;King et al 2013;Neuman et al 2013;Ferris et al 2014;Koenig et al 2014, de Grawn et al 2016. The use of controlled physical activity, as a complementary treatment, possibly improves the comfort level of the horse and decreases the inflammatory process (Kerbyson et al 2013).…”
Section: Possible Treatmentsmentioning
confidence: 99%
“…However, several studies have demonstrated significant pain post injection with monoiodoacetate, and subsequently the technique has recently fallen out of favour. Intra‐articular injection of ethanol is a suitable treatment option for pain associated with the distal tarsal joints but contrast radiography should be used to ensure that there is no communication with the tibiotarsal joint.…”
Section: Osteoarthritismentioning
confidence: 99%